Understanding Curriculum Transformation Towards Educational Innovation in The Era of All-Digital Technology - M. Syukri Azwar Lubis; Endang Fatmawati; Emy Yunita Rahma Pratiwi; Joko Sabtohadi; Antono Damayanto (Nazhruna: Jurnal Pendidikan Islam, 2022)
Through a study of several curriculum kinds of literature and educational innovations, we have understood how curriculum change in various educational institutions is. This study analyzed and discusses how policymakers prepare various strategic policies, from government documents to schools. We reviewed all documents with a phenomenological approach from curriculum transformation policy documents, from central institutional and local internal schools expecting school involvement with the change towards transformation. With curriculum transformation positioned as an innovation in a challenging digital era, the theory and application of transformational learning encourage the lens to analyze the alignment of national policies with the goal of curriculum transformation. This paper explores the extent to which the government is changing from a high-risk, subject-content-based learning approach to the curriculum. Pedagogy of learning and applications was essential to achieve more complex educational goals and active learning theory. Three phases of commitment are distinguished through an assessment rubric, offering a system for evaluating educational plan change drives. Suggestions for instructive pioneers incorporate the need to coordinate institutional techniques with disciplinary mastery and ability and the significance of language reception as a forerunner to execution.